Soil nutrients determine leaf traits and above-ground biomass in the tropical cloud forest of Hainan Island - Batool, Farwa; Bahadur, Saraj; Long, Wenxing (Frontiers in Forests and Global Change, 2024)
Identifying soil characteristics associated with the plant's resource use and acquisition strategy at different scales could be a crucial step to understanding community assembly and plant strategy. There is an increasing trend that plant functional properties can be an important driver of ecosystem functioning. However, major knowledge gaps exist about how soil abiotic properties, shape species diversity, above-ground biomass (AGB) and plant functional diversity in the Bawangling tropical forest (TCF) of Hainan island. Hence we hypothesized that plant functional traits and above-ground biomass would be strongly associated with soil abiotic factors given their direct relationship to soil resource acquisition and use. Here, we used twelve plant functional traits (FTs), above-ground biomass (AGB), and five soil nutrients in the Bawangling tropical cloud forest of Hainan Island by using a polynomial regression model and multivariate correlations to show relationship and identify how plants allocate their limited resources to adapt to their surroundings. Various phytosociological attributes were assessed and an Importance Value Index (IVI) value was calculated for each species to determine the dominant species. More than half of the total variations could be attributed to interspecific variations in H, DBH, LA, LMA and LDW. From a taxonomic perspective; we found that species-level variance was more significant for plant functional traits and soil nutrients like TN, AP, TP, and OM. On the other hand, variation in specific stem density (SSD), leaf thickness (LT), leaf phosphorus (LP) and leaf soluble sugar (LS) was an exception for these tendencies. Among soil nutrients, soil nitrogen and phosphorus significantly impact the species and functional traits. Furthermore, the soil AN and TP we also found to have a comparatively strong positive relationship with above-ground biomass (AGB) as compared with other soil nutrients. The morpho-physiological functional traits showed a trade-off between conservative and acquisitive resource usage. These variations suggested that the relationships of functional traits, AGB, and species with soil nutrients mainly AN and TP in tropical cloud forests can directly affect the growth, reproduction, and survival of the species and are beneficial for the species co-existence and maintenance of biodiversity.